2014
DOI: 10.1557/jmr.2014.289
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent mechanical behavior of free-standing glassy polymer thin films

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…T g depression observed in thin films relative to the bulk is mainly attributed to the free‐surface‐induced enhancement of segmental mobility and shift of chain relaxation . Previous experiments and molecular simulations have consistently demonstrated that the free‐surface effects on thin film T g are influenced by factors relevant to polymer chain relaxation and dynamics, such as film thickness, chain rigidity, cohesive interactions, and others . Among these factors, the role of molecular weight (MW) effects on T g ‐confinement behavior has been studied experimentally, and has also led to theoretical models such as de Gennes' sliding motion mechanism and the delayed glassification model …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T g depression observed in thin films relative to the bulk is mainly attributed to the free‐surface‐induced enhancement of segmental mobility and shift of chain relaxation . Previous experiments and molecular simulations have consistently demonstrated that the free‐surface effects on thin film T g are influenced by factors relevant to polymer chain relaxation and dynamics, such as film thickness, chain rigidity, cohesive interactions, and others . Among these factors, the role of molecular weight (MW) effects on T g ‐confinement behavior has been studied experimentally, and has also led to theoretical models such as de Gennes' sliding motion mechanism and the delayed glassification model …”
Section: Introductionmentioning
confidence: 99%
“…
relevant to polymer chain relaxation and dynamics, such as fi lm thickness, [ 5,7,8 ] chain rigidity, [ 9,10 ] cohesive interactions, [ 11,12 ] and others. [ 13 ] Among these factors, the role of molecular weight (MW) effects on T g -confi nement behavior has been studied experimentally, [14][15][16][17] and has also led to theoretical models such as de Gennes' sliding motion mechanism [ 18 ] and the delayed glassifi cation model.
…”
mentioning
confidence: 99%
“…The loading rate is around 1 Â 10 7 s À1 , falling into the conventional strain rate regime (10 7 to 10 9 s À1 ) as commonly used in molecular dynamics studies. [71][72][73] To eliminate the effect of thermal uctuations, temperature was controlled at around 1 K. Unless otherwise stated, time integration was performed on Nose-Hoover style non-Hamiltonian equations of motion from the isothermal-isobaric (NPT) ensemble, 74 in which the time step was set to 1 fs for both stability and accuracy. All the simulations were performed by implementing a parallel solver for molecular dynamics LAMMPS, 75 and the results were visualized through the OVITO 76 package.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…The addition of chemical specificity to coarse grain models has enabled simulations to begin to understand the origins of polymer chemistry dependent thermomechanical behavior under confinement . Simulations have also demonstrated that T g and moduli changes on confinement are not fully correlated, in agreement with surface wrinkling experiments . Coarse grain simulations, in general, provide a great opportunity to learn more about the local mechanical properties in confined systems as the particles can be individually tracked in the simulations to readily determine the mean square displacement < u 2 > through the Debye–Waller factor.…”
Section: Elastic Properties Of Polymer Glasses Under Confinementmentioning
confidence: 97%